2018
DOI: 10.1002/cne.24476
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrastructural analysis of fibers expressing parvalbumin, calretinin, calbindin D‐28k, stage specific embryonic antigen‐4, and phosphorylated neurofilament 200 in the peripheral sensory root of the rat trigeminal ganglion

Abstract: Parvalbumin (PV), calretinin (CR), calbindin D-28k (CB), stage specific embryonic antigen-4 (SSEA4), and phosphorylated neurofilament 200 (pNF200) have been commonly used as markers for primary afferent neurons with large myelinated (A) fibers but detailed information on the expression of these markers in specific primary afferent fiber types is still lacking. We here examined the fibers that express PV, CR, CB, SSEA4, and pNF200 in the trigeminal ganglion and its peripheral sensory root by light- and electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Since CGRP was also found in motorneurons (Marti et al, 1987; Harmann et al, 1988; Torres‐Da‐Silva et al, 2016), it was proposed that CGRP can be involved in axonal elongation as well in synapsis formation (Kim et al, 2016). Present study suggests that CGRP could be expressed in both nociceptors and mehanoceptors as was also proposed by Bae et al (2018). CGRP fibers in the spinal ventral horn form separate system which differs from that in the dorsal horn, where CGPR is brought in association with acetylcholine at neuromuscular junctions (Takami et al, 1985; New and Mudge, 1986; Tohyama and Shiotani, 1986).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Since CGRP was also found in motorneurons (Marti et al, 1987; Harmann et al, 1988; Torres‐Da‐Silva et al, 2016), it was proposed that CGRP can be involved in axonal elongation as well in synapsis formation (Kim et al, 2016). Present study suggests that CGRP could be expressed in both nociceptors and mehanoceptors as was also proposed by Bae et al (2018). CGRP fibers in the spinal ventral horn form separate system which differs from that in the dorsal horn, where CGPR is brought in association with acetylcholine at neuromuscular junctions (Takami et al, 1985; New and Mudge, 1986; Tohyama and Shiotani, 1986).…”
Section: Discussionsupporting
confidence: 75%
“…By the end of 9th–10th DW, sprouting of NF200 positive fibers indicated that NF200 participates in the formation and elongation of the SC axons which is in accordance to previous data (Oblinger, 1987). In rats NF200 is expressed in myelinated primary afferents (Lawson and Waddell, 1991) while in trigeminal ganglion small and large myelinated fibers as well as unmyelinated ones were labelled (Bae et al, 2018). Since the myelinization still does not occur in the presented investigated periods, NF200 positive fibers could be described as nonnociceptive ones.…”
Section: Discussionmentioning
confidence: 99%
“…While data about the source and structure of proprioceptors in the tongue are varied and may differ depending on species, reports suggest that trigeminal afferents may be partly involved in mediating tongue proprioception [ 54 – 57 , 61 ]. As suggested previously, similar to the DRGs, PV expressing TG neurons may be expressed in proprioceptors or low-threshold mechanoreceptors [ 62 ]. However, it is noteworthy that differences lie between PV expressing DRG and TG neurons such as PV expressing TG neurons can innervate cells other than muscle spindles [ 60 ] and that not all PV positive TG neurons are TrkC positive, suggesting differential role of PV in TG neurons (Figs 1 and 4 and [ 60 ].…”
Section: Discussionmentioning
confidence: 81%
“…Previous EM studies identified both myelinated and unmyelinated axons in dental pulp [19,20], but the authors did not elucidate where and how the morphology of the parent myelinated axons change between their origin in the TG and their target in the dental pulp, or within the dental pulp itself. It was shown that virtually all axons in the sensory roots of the TG that are immunopositive for parvalbumin (PV+) are myelinated [21]. A study using PV as a marker for myelinated axons indicated that the parent myelinated axons innervating human dental pulp undergo significant morphological changes during their peripheral course before and after they enter the dental pulp [3].…”
Section: Morphological Features Of Axons Within the Dental Pulpmentioning
confidence: 99%